The performance of an in-house loop-mediated isothermal amplification for the rapid detection of Mycobacterium tuberculosis in sputum samples in comparison with Xpert MTB/RIF, microscopy and culture - Phetsuksiri, Benjawan (2020)
Simple, low-cost and effective diagnostic tests for tuberculosis (TB) are needed especially in TB-high burden settings. The present study evaluated the performance of an in-house loop-mediated isothermal amplification (LAMP) for diagnosing TB by comparing it to Xpert MTB/RIF, microscopy and culture. In Thailand, a total of 204 excess sputum samples volume after the processing of cultures were used for Mycobacterium tuberculosis (MTB) detection by Xpert MTB/RIF and LAMP. Based on culture results as the gold standard, the overall sensitivity of LAMP and Xpert MTB/RIF were 82.1% (126/153; 95% confidential interval [CI]: 75.4-88.98%) and 86.9 % (133/153; 95% CI: 80.5-90.8%) respectively, and the specificity of both tests was 100% (51/51; 95% CI: 93.0-100.0%). In comparison with Xpert MTB/RIF, the sensitivity and specificity of LAMP were 94.7% (126/133; 95% CI: 89.5-97.9%), and 100.0% (73/73; 95% CI: 94.9-100.0%), respectively. The average threshold cycle (Ct) of Xpert MTB/RIF detection for positive and negative LAMP results was statistically different, of 18.4 and 27.0, respectively (p < 0.05). In comparison with the acid-fast staining technique, and analyzing LAMP and Xpert MTB/RIF in smear-negative/ culture-positive specimens, there was an increase of the detection rate by 47.7% (21/44) and 54.6% (24/44). The diagnostic sensitivity and specificity of LAMP appeared to be comparable to those of Xpert MTB/RIF. We claim that this LAMP has potential to provide a sensitive diagnostic test for the rapid TB diagnosis. It allowed a fast detection of MTB before the cultures and it could be used in resource-limited laboratory settings.